2002
DOI: 10.1074/jbc.m208647200
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Surface Accessibility of a Pore-lining Threonine Residue (T6′) in the Glycine and GABAA Receptors

Abstract: The substituted cysteine accessibility method was used to probe the surface exposure of a pore-lining threonine residue (T6) common to both the glycine receptor (GlyR) and ␥-aminobutyric acid, type A receptor (GABA A R) chloride channels. This residue lies close to the channel activation gate, the ionic selectivity filter, and the main pore blocker binding site. Despite their high amino acid sequence homologies and common role in conducting chloride ions, recent studies have suggested that the GlyRs and GABA A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…Although 100:400 M Cu:phen applied in the closed or open states had no effect on current magnitude, a 2-min application of 10 mM DTT in the closed state caused a weak transient potentiation that is most likely a pharmacological action (13). In contrast, the ␣ T6ЈC ␤…”
Section: Electrophysiological Properties Ofmentioning
confidence: 75%
See 1 more Smart Citation
“…Although 100:400 M Cu:phen applied in the closed or open states had no effect on current magnitude, a 2-min application of 10 mM DTT in the closed state caused a weak transient potentiation that is most likely a pharmacological action (13). In contrast, the ␣ T6ЈC ␤…”
Section: Electrophysiological Properties Ofmentioning
confidence: 75%
“…The total rotational movement, which was proposed to be around 120 o , is not easily reconciled with other studies. Specifically, Horenstein et al (12) In apparent contrast, an electrophysiological analysis of the effects of oxidizing and reducing agents on the same GABA A R subunits recombinantly expressed in HEK293 cells suggested that 6Ј cysteines efficiently formed disulfide bonds in the closed state and in the desensitized state (13). This suggests that the functional properties of identical ␣ T6ЈC ␤ T6ЈC GABA A Rs vary dramatically between the Xenopus oocyte and the HEK293 cell expression systems.…”
Section: T6cmentioning
confidence: 93%
“…8). Although the precise location of the gate has been equivocal (8,13), the 4-Å density map of the nAChR (6) and recent MTS studies with glycine, ␥-aminobutyric acid, type A, and 5-HT 3 receptors implicate movement between the 6Ј and 13Ј positions (7,9,10,57). In support of this, linear free energy relationship analysis of mutant nAChRs suggested that the cytoplasmic side of M2 moves last upon activation after a wave of energy moving from the site of ligand binding down toward the cytoplasmic selectivity filter (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…In the GlyR, residues in the M2-M3 loop, as well as the M1-M2 loop, were shown to be involved in gating (46). In addition, changes in the accessibility of residues the M2-M3 linker in GlyR and GABA A R as a function of the activation state of the receptor suggests a movement of M2-M3 loop in gating (44,47). Specific residues in the ligand-binding domain that interact with distinct residues on the M2-M3 loop of GABA A R, coupling agonist binding to channel gating, have been identified, and the interaction of the ligand-binding domain with the transmembrane domains has been elegantly modeled (48).…”
Section: Minireview: Glyr Structure and Function 19384mentioning
confidence: 99%
“…In addition, differential accessibilities to labeling reagents in SCAM studies have illustrated many of the structural changes in the resting, open, and desensitized state of the receptor (15,44). Photolabeling studies of the nAChR also showed differential accessibility of residues in the ␣ 1 subunit in open, closed, and desensitized states, particularly in the signature Cys-loop (45).…”
Section: Channel Gatingmentioning
confidence: 99%